10000‐Fold Enhancement in Proton Conduction by Doping of Cesium Ions in a Proton‐Conducting Zwitterionic Metal–Organic Framework. Issue 27 (20th June 2016) - Shalini, Sorout; Aggarwal, Shubhangi; Singh, Santosh K.; Dutt, Malvika; Ajithkumar, Thallaseril G.; Vaidhyanathan, Ramanathan
Abstract : Developing metal–organic framework (MOF)‐based proton‐conducting electrolytes for fuel‐cell applications is an important target that has drawn a lot of attention. A key approach involves the selective replacement of the guest species within the pores to enhance performance. The modular and crystalline nature of the MOF permits controlled introduction of such species and characterization of their compositions with high precision, a task which is very difficult to achieve in amorphous polymers. Herein, we partially replaced the protons of a zwitterionic pyridinol in Mg(terephthalate)(pyridinol) MOF1 with Cs + ions, which brought about a 10000‐fold increase in the proton conductivity (10 –6 to 10 –2 S cm –1 ). Interestingly, Li + ions could not be loaded, whereas Cs + ions with smaller hydrated ionic radii could be loaded, and the loading was controlled as a function of time. The Cs + loading nearly halved the activation energy (from 0.35 for1 to 0.19 eV for1 _Cs). The highest conductivities were realized for an optimal loading of Cs + ions, which was found to be about 10 % in this case. Abstract : Partial replacement of protons from a zwitterionic pyridinol of a Mg(terephthalate) metal–organic framework by about 10 % Cs + ions provides a 10000‐fold enhancement in proton conductivity. The concentration of Cs + needs to be optimal to realize this maximum enhancement.